A Clinical Study on Evaluation of Vertical Accuracy of Interocclusal Registration Materials in Centric Relation—An In Vivo Study - Bansri Tank; Rupal J. Shah; Gunjit Marwaha; Neelima Chauhan; Ekta Chheda; Om Shah (Journal of Pharmacy and Bioallied Sciences)
Background: The precise recording and transfer of maxillo-mandibular relationships are pivotal in prosthetic treatments. Aims and Objectives: To evaluate the efficacy of four bite registration materials: alu wax, hard wax, polyvinylsiloxane, and bis-acrylic resin, in accurately recording, maintaining, and reproducing the vertical interocclusal relationship on either side of the dentition. Materials and Methods: Thirty subjects within the age group of 20–45 years were selected. The difference in the reading of the vertical distance with the material and at maximum intercuspation is calculated individually for each record on the left and right sides. Results: On the right side, the lowest mean was observed in MIP and the highest in hard wax. On the left side, the lowest mean was observed in MIP, while the highest was in alu wax. Among the four bite registration materials evaluated, Luxabite and Jetbite exhibited the highest mean accuracy scores. Conclusions: Closure on interocclusal record material and bite release produce vertical discrepancies. Waxes showed the most, and bis-acrylic Luxabite and addition silicones showed the least dimensional distortion vertically.